How to Foresee and Measure the Real Economic Impact of a Lean Manufacturing Implementation (2013)
The academic and industrial worlds seem to agree in the convenience of implementing Lean Manufacturing. Arguments to highlight the benefits of implementing Lean usually include testimonials from successful companies, published case studies, even conference presentations, plant tours, and television programs. It is not easy to foresee the impact of a Lean implementation in strictly monetary terms. Lean is an operational philosophy that does more than saving money; it prepares companies for sustained improvement and creates disciplines and operational capabilities, yet it could be argued that these capabilities are hard to value and quantify. In this paper, we propose a flowchart-type methodology to decide if a change in a procedure, in the use of tangible resources or in the use of time brought about by the implementation of a Lean Manufacturing technique will have a measurable economic impact. The decision maker will need to know the specific circumstances of the production system, but we believe he will be able to predict the economic impact of a Lean implementation (or to evaluate the results of an ongoing Lean project) with more precision, to build a stronger and more comprehensible business case and convince upper management of the real benefits of Lean.